Association between lifetime and recent stressful life events and the early course and psychopathology in patients with newly diagnosed bipolar disorder, first‐degree unaffected relatives and healthy controls: Cross‐sectional results from a prospective study. (13th May 2021) - av Kák Kollsker, Stina; Coello, Klara; Stanislaus, Sharleny; Melbye, Sigurd; Lie Kjærstad, Hanne; Stefanie Ormstrup Sletved, Kimie; Vedel Kessing, Lars; Vinberg, Maj
Abstract: Objective: There is an accumulation of stressful life events prior to the first mood episode, but the impact of previous severe life events on psychopathology in patients with bipolar disorder (BD) is not well studied. We aimed to examine the number of recent and lifetime life events in patients with newly diagnosed BD, their unaffected relatives (UR), and healthy controls (HC) as well as the impact of severe lifetime life events on the early course of BD. Methods: We compared the number of recent and lifetime life events in 398 patients with newly diagnosed BD, 109 UR, and 214 HC. We subsequently dichotomized the patients with BD by >2 lifetime life events to investigate the associations of severe lifetime life events with clinical characteristics and affective symptoms. Results: Patients with newly diagnosed BD reported significantly more life events in the last 12 months and lifetime before compared with UR and HC. Patients who reported >2 lifetime life events ( n  = 160) compared with patients with 0–2 life events ( n  = 238) had a significantly longer diagnostic delay (9.5 years ± 8.2 vs. 6.2 years ± 6.9), presented with more anxiety and depressive symptoms and had at least one previous suicide attempt (30.6% vs. 15.6%) and one previous admission (51.3% vs. 36.6%). Conclusion: The experience of severe lifetime life events seems to impact the early course in BD in terms of longer diagnostic delay, more severe psychopathology including more admissions and a more than doubled risk for previous suicide attempts.